2016
DOI: 10.1007/978-1-4939-3040-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Comparative Assay of Human Mitochondrial Single-Stranded DNA-Binding Protein

Abstract: The mitochondrial single-stranded DNA-binding protein (mtSSB) coordinates the function of replisome components at the mitochondrial replication fork. In recent years, it has been demonstrated that mtSSB stimulates the activities of DNA polymerase γ (Pol γ) and mitochondrial DNA (mtDNA) helicase in a concentration-dependent manner. Here we present a new approach to purify the human mtSSB and our standard assays to evaluate its biochemical properties, including a Gel Mobility Shift Assay (GMSA) to assess single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The TWINKLE helicase encoded by TWNK gene is a mitochondrial 5'‐3’ helicase, which can bind to double‐stranded DNA (dsDNA), and dissociate it into single‐stranded DNA by breaking the hydrogen bond between the annealed nucleotide bases 18 . Besides, TWINKLE helicase can cooperate with Polγ to participate in the replication of mtDNA 19 . Peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α), a transcriptional coactivator with multiple functional activities, plays a major role in the regulation of cellular energy homeostasis and mitochondrial oxidative metabolism 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TWINKLE helicase encoded by TWNK gene is a mitochondrial 5'‐3’ helicase, which can bind to double‐stranded DNA (dsDNA), and dissociate it into single‐stranded DNA by breaking the hydrogen bond between the annealed nucleotide bases 18 . Besides, TWINKLE helicase can cooperate with Polγ to participate in the replication of mtDNA 19 . Peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α), a transcriptional coactivator with multiple functional activities, plays a major role in the regulation of cellular energy homeostasis and mitochondrial oxidative metabolism 20 .…”
Section: Introductionmentioning
confidence: 99%
“… 18 Besides, TWINKLE helicase can cooperate with Polγ to participate in the replication of mtDNA. 19 Peroxisome proliferator‐activated receptor γ coactivator‐1α (PGC‐1α), a transcriptional coactivator with multiple functional activities, plays a major role in the regulation of cellular energy homeostasis and mitochondrial oxidative metabolism. 20 Studies have shown that PGC‐1α regulates the transcription of the mitochondrial genome by binding with NRF‐1 and NRF‐2 and activating the expression of the downstream genes TFAM , TFB1 M and TFB2 M that regulate the replication and transcription of mitochondrial DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The TWNK gene, also known as C10orf2 or PEO1, is responsible for encoding TWIN-KLE, an mtDNA helicase, an enzyme that unwinds DNA temporarily for replication [56]. The dysfunction in TWINKLE is thought to pause or stall mtDNA replication and accumulate many mtDNA deletions over time [57].…”
Section: Twinkle Mtdna Helicase (Twnk)mentioning
confidence: 99%
“…TWINKLE is a mitochondrial 5′-3′ helicase necessary for replication of human mitochondrial DNA (Milenkovic et al 2013 ; Tyynismaa et al 2004 ). It binds to and unwinds double-stranded DNA (dsDNA) by breaking hydrogen bonds between annealed nucleotide bases and separating to single strands (Tyynismaa et al 2005 ; Korhonen et al 2003 ; García-Gómez et al 2013 ; Cieskielski et al 2016 ; Lamantea et al 2002 ).…”
Section: Genes Encoding Proteins Involved In Mitochondrial Dna Replicmentioning
confidence: 99%